Energy sector investment modeling under uncertainty for RA from the view of energy security - Ani Khalatyan (European Regional Science Association (ERSA), 2014)
The Armenian economy has been growing strongly in recent years. The country has successfully implemented a comprehensive stabilisation and a structural reform program in energy sector. Although now Armenia almost completely depends on imported energy. The most domestically produced primary energy is electricity from hydroelectric plants and one nuclear power plant. However, there are serious challenges: a. Sufficient electricity service b. Energy safety c. Maintenance of electricity service availability for consumers at the same time providing the financial vitality of the sector.
Keywords: 330